Serum Uric Acid Is Associated with Metabolic Syndrome and Insulin Resistance among Health Personnel from Peru - Brenda M. Galindo-Yllu; Ricardo Rojas-Humpire; Carlos J. Toro-Huamanchumo; Rosmery Gutierrez-Ajalcriña; Anderson N. Soriano (Journal of Nutrition and Metabolism)
We explored the association between serum uric acid (SUA) and metabolic syndrome (MetS) and insulin resistance (IR) among health personnel from a public hospital in Peru in a cross-sectional study with data from the Plan for the Prevention and Surveillance of Communicable and Noncommunicable Diseases of Huaycán Hospital. MetS was defined according to Latin American Diabetes Association (ALAD) criteria and IR with surrogate IR markers, triglyceride-to-HDL-C ratio (TG/HDL-C), and triglyceride-to-glucose index (TyG). The association between SUA and MetS and IR was determined using Poisson regression models in a sample of 292 participants with an average age of 46.2 ± 10.6 years. The total prevalence of MetS was 38%, and the individuals with MetS presented mainly alterations in anthropometric parameters (obesity and body fat). Finally, the adjusted regression models showed that women with SUA in the highest tertile increased the prevalence of MetS (PR: 1.71, 95% CI: 1.07–2.74) compared to the lowest tertile of SUA in women, while SUA increased hypertriglyceridemia and IR (TG/HDL-C and TyG) in both sexes. We concluded that SUA is strongly associated with MetS in women, and SUA increases hypertriglyceridemia and IR in both sexes. On the contrary, more research is required regarding the female population.